2011
DOI: 10.5586/asbp.2007.013
|View full text |Cite
|
Sign up to set email alerts
|

Anthracene derivatlves in some species of Rumex L genus

Abstract: Eight anthracene derivatives (chrysophanol, physcion, emodin, aloe-emodin, rhein, barbaloin, sennoside A and sennoside B) were signified in six species of Rumex L. genus: R. acetosa L., R. acetosella L., R. confertus Willd., R. crispus L., R. hydrolapathum Huds. and R. obtusifolius L. For the investigations methanolic extracts were prepared from the roots, leaves and fruits of these species. Reverse Phase High Performance Liquid Chromatography was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Eight anthracene derivatives were described in six Rumex species (Table 7), including R. acetosa, R. acetosella, R. crispus and R. obtusifolius, and the highest levels were detected in the roots (Smolarz et al, 2011).…”
Section: Phenanthrenes and Hydroxyanthracenesmentioning
confidence: 99%
“…Eight anthracene derivatives were described in six Rumex species (Table 7), including R. acetosa, R. acetosella, R. crispus and R. obtusifolius, and the highest levels were detected in the roots (Smolarz et al, 2011).…”
Section: Phenanthrenes and Hydroxyanthracenesmentioning
confidence: 99%
“…acetosa., R. acetosella L., R. confertus Willd., R. crispus L., R. hydrolapathum Huds. R. obtusifolius [41] and R. aquaticus [42], compounds 5 and 7 from R. japonicus [43], R. nepalensis [44], compound 8 from R. obtusifolius [45] and compounds 7 and 8 from R. acetosa [46]. Base to the fact that, anthraquinones represent one of the main classes of secondary metabolites isolated from the genus Rumex [14] [47], their presence in all of the above species allowed us to conclude that R. abyssinicus and the other species mentioned exhibit very close chemotaxonomic relationships.…”
Section: Chemophenetic Significancementioning
confidence: 99%
“…In TM the leaves of R. acetosella are used by the native populations of North America as treatment for warts and bruises. The aerial parts contribute to amelioration of diarrhea and stomach disorders in North America and Hungary, while seeds are used to treat diarrhea and dysentery in Hungary (Chevalier, 1996;Shale et al, 1999;Foster et al, 2000;Wegiera et al, 2007;Vasas et al, 2015). An ethnobotanical survey of medicinal plants used in Turkey revealed that leaves of R. acetosella are used traditionally as an analgesic and diuretic (Cakilcioglu and Turkoglu, 2010).…”
Section: R Acetosella L-red Sorrel Polygonaceaementioning
confidence: 99%
“…The main chemical compounds in the genus Rumex are antraquinones (emodin, physcion, and chrysophanol in fruits and leaves, and sennoside A in fruits and roots), nepodin, and flavanoids (quercetin-3-O-glucoside) with important antioxidant activity, while the stilbenoids demonstrated to have a positive impact in cancer therapy and inflammatory diseases (Wegiera et al, 2007;Vasas et al, 2015).…”
Section: R Acetosella L-red Sorrel Polygonaceaementioning
confidence: 99%